2023
DOI: 10.1002/chir.23562
|View full text |Cite
|
Sign up to set email alerts
|

d‐Amino acids in biological systems

Abstract: Investigations on the occurrence and biochemical roles of free D‐amino acids and D‐amino acid‐containing peptides and proteins in living systems have increased in frequency and significance. Their occurrence and roles may vary substantially with progression from microbiotic to evermore advanced macrobiotic systems. We now understand many of the biosynthetic and regulatory pathways, which are outlined herein. Important uses for D‐amino acids in plants, invertebrates, and vertebrates are reviewed. Given its impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 354 publications
(612 reference statements)
0
10
0
Order By: Relevance
“…In fact, considering that the main target of proteolytic phenomena is the peptide bond, the reversal of the sequence, with the concomitant use of d -amino acids, results in retro-inverso modification and will no longer be recognized by most proteases. However, as reported in a recent review, enzymes that are able to recognize d -amino acids such as racemase, transaminases, oxidases, and dehydrogenases have been identified in the human body, even if their production and metabolism in mammalians is lower than in other species, e.g., bacteria . Finally, we underline that all of the in vitro and ex-vivo studies described in this paper were conducted following a rational approach based on the quantitative analysis of experiments conducted by scientific methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, considering that the main target of proteolytic phenomena is the peptide bond, the reversal of the sequence, with the concomitant use of d -amino acids, results in retro-inverso modification and will no longer be recognized by most proteases. However, as reported in a recent review, enzymes that are able to recognize d -amino acids such as racemase, transaminases, oxidases, and dehydrogenases have been identified in the human body, even if their production and metabolism in mammalians is lower than in other species, e.g., bacteria . Finally, we underline that all of the in vitro and ex-vivo studies described in this paper were conducted following a rational approach based on the quantitative analysis of experiments conducted by scientific methods.…”
Section: Discussionmentioning
confidence: 99%
“…However, as reported in a recent review, enzymes that are able to recognize D-amino acids such as racemase, transaminases, oxidases, and dehydrogenases have been identified in the human body, even if their production and metabolism in mammalians is lower than in other species, e.g., bacteria. 39 Finally, we underline that all of the in vitro and ex-vivo studies described in this paper were conducted following a rational approach based on the quantitative analysis of experiments conducted by scientific methods. This should be considered an added value in the design of new cosmeceutical ingredients, whose claims are rarely supported by appropriate studies but rather anecdotally reported.…”
Section: Journal Of Medicinal Chemistrymentioning
confidence: 99%
“…Early work on AA enantioseparations 9–11 propelled the field of chiral chromatography to its modern form and initiated studies regarding the d -enantiomer, which was originally thought not to be relevant to biological systems. Now, d -enantiomers have been detected in a variety of biological environments, 12 have been shown to play roles in neurological development/biological regulation, 12–15 and serve as potential disease biomarkers. 16 The importance of the chirality of amino acids has driven many analytical procedures to be reported in the literature over the past five decades, 9–11,17–20 with some of this research focusing on or mentioning greenness/sustainability.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, numerous occurrences of D-AA have been found at different positions of bioactive peptides or proteins and in natural products [ 7 ]. Smaller amounts of free D-AAs are found in essentially all biological systems [ 8 ], sometimes playing vital roles and frequently being disease biomarkers [ 9 ].…”
Section: Introductionmentioning
confidence: 99%